2009
DOI: 10.1002/lary.20703
|View full text |Cite
|
Sign up to set email alerts
|

Complications of midline‐open tracheotomy in adults

Abstract: Objectives/Hypothesis: Percutaneous tracheotomy is progressively replacing open tracheotomy as a consequence of promising results of comparative studies. However, this comparison has four considerable weaknesses: 1) selected indications (high-risk patients excluded for percutaneous tracheotomy); 2) varying spectra of complications included in different studies; 3) varying operative settings (experienced surgeons exclusively, surgeons in training, or both); and 4) missing differentiation between different surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…However, the fact that mortality following tracheotomy is higher in cardiac conditions and lower conditions such as muscular dystrophy and upper airway infection strongly suggests that the tracheotomy itself is rarely the cause of death 5, 6. This is certainly in accord with the authors' personal experiences, in that most patients who die with a tracheotomy in place die of an underlying disease rather than a tracheotomy complication 7, 8…”
Section: Discussionmentioning
confidence: 60%
“…However, the fact that mortality following tracheotomy is higher in cardiac conditions and lower conditions such as muscular dystrophy and upper airway infection strongly suggests that the tracheotomy itself is rarely the cause of death 5, 6. This is certainly in accord with the authors' personal experiences, in that most patients who die with a tracheotomy in place die of an underlying disease rather than a tracheotomy complication 7, 8…”
Section: Discussionmentioning
confidence: 60%
“…Newer studies have reported lower complication rates of around 9-15 % [8,9]. The likelihood of complication increases significantly when it is performed in emergency setting [5].…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding vessel in thyroid substance was tied off in one patient, while diffuse ooze from peritracheotomy surface was managed with pressure packing in the second. The third patient had on and off ooze from peristomal region and was managed with local (9) hemostatic measures. Patients with posttracheotomy subcutaneous emphysema were managed successfully with observation.…”
Section: Outcomementioning
confidence: 99%
“…Open tracheotomies are safe procedures even when performed in high‐risk patients by inexperienced surgeons 1. Reported complications associated with the well‐known percutaneous dilatational tracheotomy (PDT) techniques are due to either predilatory dissection or the downward forces applied to the surrounding tissues and posterior tracheal wall during dilation 2.…”
Section: Introductionmentioning
confidence: 99%